IMPLEMENTASI RENCANA STRATEGIS DINAS PERIKANAN, KELAUTAN DAN PERTANIAN KOTA BONTANG SEBAGAI UPAYA MEWUJUDKAN PENGELOLAAN POTENSI WILAYAH PESISIR DAN LAUT KOTA BONTANG BERWAWASAN LINGKUNGAN - Kus Indarto, Mr. (FIA UB, 2012)
Regional autonomy gave authority to local government to perform marine area resources. This provide an opportunity for region to be able to utilize the resources of marine area to improve local economic growth. But, behind the authority, of course there is a responsibility for protecting the environment. In this regard, Bontang Municipality (in this case conducted by The Fisheries, Marine and Agriculture Department) as having the resources of coastal and marine are seeks to manage the existing potentials/resources environmentally insightfully. This study sought to describe and analyze the implementation of the Strategic Plan as a public policy that has been set. The purposes of this study are to describe and analyze: (1) Implementation of the Fisheries, Marine and Agriculture Department Strategic Plan of Bontang Municipal as effort to realize potential management of coastal and marine of Bontang Municipal environmentally insightfully; (2) The supporting and inhibiting factors in implementation of Fisheries, Marine and Agriculture Department Strategic Plan of Bontang Municipality. The findings in the field showed that the implementation of the Fisheries, Marine and Agriculture Department Strategic Plan of Bontang Municipal include: a. scanning, b. the mission,; c. strategy, and d. program, design or blueprint for implementation of the strategy. This study found that the implementation of strategic plan the Fisheries, Marine and Agriculture Department has been running very well or very successful. There are factors that influence the implementation of the Fisheries, Marine and Agriculture Department Strategic Plan of Bontang Municipal. Supporting factors are: a. the existence of qualified human resources; b. the commitment of Bontang Municipality; c. resources of coastal and marine areas are abundant. While the inhibiting factors are: the absence of City Spatial Plan (City Spatial); and b. lack of public awareness that influence their participation